Functionalized single-walled carbon nanohorns to reinforce sulfonated poly(ether ether ketone) electrolyte for direct methanol fuel cells - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, SreeKuttan M. (ChemElectroChem, 2020)
Carbon-nanomaterial-based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single-wall carbon nanohorns (f-SWNHs) are realized as an additive in sPEEK. The -COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f-SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f-SWNHs shows improved electrochemical selectivity of 17.03x10(-4) Scm(-3)s and delivers the highest peak power density of 230 mW cm(-2)in DMFCs.
Keywords: carbon nanohorns; direct methanol fuel cells; membrane electrolyte; proton conductivity; sulfonated poly ether ether ketone

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry